Odpowiedzi

2010-01-18T19:12:19+01:00
A) x²+6x+9-2(3x+9-x²-3x)+4(9x²-6x+1)=x²+6x+9-6x-18+2x²+6x+36x²-24x+4=39x²-18x-5
b)4-x²-4(4x²-4x+1)+2(x²+6x+9)=4-x²-16x²+16x-4+2x²+12x+18=18-15x²+28x
2010-01-18T19:23:10+01:00
A)
(x+3)^ - 2(3-x) (x+3) + 4 (3x -1)^=
x^+9 -2(3x+9-x^-3x) + 4(9x^+1)=
x^+9 -18+2x^+36x^+4=
37x^-5

b)
(2 -x) (x+2) - 4 (2x -1)^ +2 (x+3)^=
2x+4-x^-2x - 4(4x+1) +2(x^+9)=
2x+4-x^-2x - 16x -4 +2x^+18=
x^-16x+18
2010-01-18T19:30:14+01:00
A)=39x^-6x-10

(x+3)^ - 2(3-x) (x+3) + 4 (3x -1)^=
(x+3)(x+3)-2[3x+9-x^-3x]+4[(3x-1)(3x-1)=
x^+3x+3x+9-18+2x^+4[9x^-3x-1]=
x^+6x-9+2x^+36x^-12x-1=
39x^-6x-10

b)=28x+26-7x^26-7x^


(2 -x) (x+2) - 4 (2x -1)^ +2 (x+3)^=
(2 -x) (x+2) - 4 (2x -1)^ +2 (x+3)^=
2x+4-x^-2x-4[(2x-1)(2x-1)]+2[(x+3)(x+3)]=
2x+4-x^-2x-4[2x^-2x-2x-1]+2[x^+3x+3x+9]=
2x+4-x^- 2x-8x^+8x+8x+4+2x^+6x+6x+18=
28x+26-7x^